ADMINISTRASI DAN SUPERVISI PENDIDIKAN ISLAM: INTEGRASI DEEP LEARNING DENGAN KURIKULUM BERBASIS CINTA PADA SEKOLAH DASAR - Serly Monica; Enjel Panesa Ratu Anggalia; Latifa Hurin Nabila Utami; Ahmad Zainuri; Frika Fatimah Zahra (CV. ADIBA AISHA AMIRA, 2025)
This study focuses on the integration of deep learning technology with a love-based curriculum in the context of Islamic education administration and supervision at the primary school level. The purpose of this study is to analyse effective integration models between adaptive learning technology and Islamic values and humanistic approaches in education. To support an effective and efficient education process, this study was conducted using a qualitative approach and systematic literature review covering international and national academic journals, reference books, and education policy documents from 2010 to 2024. The results of the study indicate that the integration of deep learning with a love-based curriculum requires a holistic framework that includes five main dimensions: (1) personalisation of learning with loving teacher guidance, (2) learning Islamic values with the help of interactive technology, (3) monitoring students' emotional well-being through an analytical system, (4) collaborative learning that develops social-emotional competencies, and (5) constructive feedback that combines AI analysis with humanistic guidance. The role of Islamic education administration includes developing balanced policies, investing in infrastructure and human resources, developing Islamic digital content, and building a learning ecosystem that integrates technology with Islamic values. Educational supervision serves to ensure that technology is used as a tool for empowerment, not as a substitute for the role of teachers as murabbi. This study concludes that successful integration depends on a commitment to maintaining the essence of Islamic education as a holistic tarbiyah process, developing intellectual, emotional, and spiritual intelligence simultaneously. Practical implications include recommendations for teacher professional development, integrated curriculum design, a holistic evaluation system that measures not only academic achievement but also student character development and well-being, and a phased implementation model that can be adapted to the context of Islamic primary schools in Indonesia.